SUCCESSFULLY TREATED INFERTILITY IN A PATIENT WITH TURNER SYNDROME WITH IN VITRO FERTILIZATION WITH DONATED EGG – A CASE REPORT - Georgievska, Jadranka; Tofoski, Gligor; Daneva Markova, Ana; Buklievska Adrijana (Македонско лекарско друштво = Macedonian Medical Association, 2020)
We present a case of a 34-year-old woman, diagnosed with Turner syndrome at the age of 18 because of short stature and irregular menstrual cycle. After the diagnosis had been established, she started with hormonal therapy for regulation of the menstrual cycle. When she got married at the age of 32 she wanted to conceive, but it was not successful and after one year she decided to make in vitro fertilization with a donated egg. It was successful in the first attempt. Her high-risk pregnancy was followed up by her gynecologist and obstetrician in atertiary level institution. The pregnancy was normal, without complications. During the pregnancy examinations at the University Clinic for Cardiology in Skopje were made and cardiovascular diseases were excluded. In 39 week of gestation an elective Caesarean section was made at the University Clinic for Gynecology and Obstetrics in Skopje, R. N. Macedonia. On 28th of February 2019 she delivered a healthy baby boy with birth weight of 2950 gr and birth length of 48 cm, with Apgar scores 8 and 9 at 1 and 5 min, respectively. No severe complications occurred during the postpartum period. By application of new assisted reproductive techniques such as in vitro fertilization with a donated egg, women with Turner syndrome and infertility can resolve their problem and fulfill their wish to have a baby.
Keywords: Turner syndrome; pregnancy; in vitro fertilization; donated egg